2016
DOI: 10.1063/1.4958693
|View full text |Cite
|
Sign up to set email alerts
|

Zn precipitation and Li depletion in Zn implanted ZnO

Abstract: Articles you may be interested inEffect of implanted species on thermal evolution of ion-induced defects in ZnO Ion implantation of Zn substituting elements in ZnO has been shown to result in a dramatic Li depletion of several microns in hydrothermally grown ZnO. This has been ascribed to a burst of mobile Zn interstials. In this study, we seek to understand the reason behind this interstitial mediated transient enhanced diffusion in Li-containing ZnO samples after Zn implantation. ZnO wafers were implanted wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 15 publications
1
2
0
Order By: Relevance
“…It should be noted that substantial defect annealing occurs within a short period of time as seen from the comparison of 5 s and 30 min anneal data at 800 °C in figure 1(a). Such behavior of ion-induced defects under RTP annealing is not surprising and previously was observed in ZnO implanted with Zn [28] and rare earth ions [29]. It was demonstrated also that transient processes of defect reconstruction and defect diffusion can occur supported by our results as shown below.…”
Section: Resultssupporting
confidence: 90%
“…It should be noted that substantial defect annealing occurs within a short period of time as seen from the comparison of 5 s and 30 min anneal data at 800 °C in figure 1(a). Such behavior of ion-induced defects under RTP annealing is not surprising and previously was observed in ZnO implanted with Zn [28] and rare earth ions [29]. It was demonstrated also that transient processes of defect reconstruction and defect diffusion can occur supported by our results as shown below.…”
Section: Resultssupporting
confidence: 90%
“…The RBS data also substantiate the redistribution of Ge observed by SIMS, and that 600 • C is not sufficient to promote Ge and Zn self-diffusion with an associated crystal recovery. Interestingly, 800 • C is in the temperature range where Zn self-interstitials (Zn I ) are released from implantation induced defect clusters [27][28][29], and this may catalyse the Ge migration and formation of the Ge nanocrystals.…”
Section: Resultsmentioning
confidence: 99%
“…For example, it was demonstrated that Zn precipitation formation and Li depletion are well correlated in Zn implanted ZnO single crystals. 38 Specifically for Er, a formation/dissociation of optically active defect centers in the course of annealing can play a role. 21 Furthermore, a large strain can be accumulated in heavily damaged crystals and it was shown that this strain may act as a driving force for defect transformation with increasing ion fluence.…”
Section: Journal Of Applied Physicsmentioning
confidence: 99%